EFFECT OF COMPETENCE AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE EDUCATION OFFICE - Sudirman Sudirman; Gergonia P Ohoiledwarin; Rachma Yuliana; Deddy Novie Citra Arta; Hartanto Hartanto (Bajang Institute, 2023)
The purpose of this research is to analyze effect of competence and discipline on employee performance at the Education Office. This type of research is correlational research. The sampling technique in this study is the census method or sampling using saturated sampling method. The population in this study are employees at the Education Office in Medan City, totaling 62 people, thus the total population being the research sample is 62 people. In this research plan, a survey method will be used and a questionnaire instrument technique will be used. Data analysis using multiple linear regression analysis. The results of the study show that competence has a positive and significant effect on employee performance at the Education Office. Discipline has a positive and significant effect on employee performance at the Education Office.